Efficacy of Tuberculosis Treatment in Patients with Drug-Resistant Tuberculosis with the Use of Bedaquiline: The Experience of the Russian Federation - Anna Starshinova; Irina Dovgalyk; Ekaterina Belyaeva; Anzhela Glushkova; Nikolay Osipov; Dmitry Kudlay (MDPI AG, 2022)
In the conditions of the continued growth of multiple- and extensive drug-resistant tuberculosis, use of the new highly effective anti-tuberculosis drugs in this patient category is of great relevance. The aim of the study was determination the efficacy of treatment in patients with multidrug- and extensive drug-resistant tuberculosis using bedaquiline based on studies published in the Russian Federation. Materials and methods: The authors analyzed data published in studies from 2014 to 2022; 41 publications were included in total and 17 articles corresponded to the study design. The results of treatment of 1404 tuberculosis patients with MDR/XDR TB were described. Bedaquiline was used according to the standard scheme with a description of the treatment results after 24-26 weeks. Treatment efficacy was estimated according to accepted criteria. Results of the study: The analysis showed that the treatment efficacy on conversion was achieved in 79.5% of cases (95% Cl 76.5-82.3), and recovery was observed in 82.0% of cases (95% Cl 78.6-85.1). Departure from the therapy was observed in rare cases (9.8%; 95% Cl 7.9-12.2). Deaths were recorded in 6.5% of cases (95% Cl 4.9-8.3), which were associated with the severe disease and concomitant pathology in 74.3%. The development of adverse events was noted in half of the patients (55.7%); however, bedaquiline cancellation occurred in a few cases (7.0%; 95% Cl 3.0-13.0). From analyzing data in patients with MDR and XDR TB, the efficacy of treatment was 89.9% (95% Cl 85.9-93.2) and 71.9% (95% Cl 66.2-77.1), respectively. Conclusion: Use of bedaquiline in treatment makes it possible to achieve recovery of patients with MDR/XDR TB in 82.0% of cases with patients dropping out of treatment in 9.8%. At the same time, in patients with MDR TB, recovery was achieved in 89.9% of cases, while in patients with XDR TB, 71.9% of cases recovered.